2021
DOI: 10.1093/jac/dkab057
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin pharmacokinetics in saliva as measured by a mobile microvolume UV spectrophotometer among people treated for rifampicin-resistant TB in Tanzania

Abstract: Background Early detection and correction of low fluoroquinolone exposure may improve treatment of MDR-TB. Objectives To explore a recently developed portable, battery-powered, UV spectrophotometer for measuring levofloxacin in saliva of people treated for MDR-TB. Methods Patients treated with levofloxacin as part of a regimen for MDR-TB in Northern Tanzania … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Over 60 years old in patients receiving levofloxacin there was a higher incidence of adverse reactions to prevent infection treatment mainly includes: the main reasons for elderly patients with viscera function decline, easily complicated by a variety of disease, and levofloxacin by kidney metabolism, effects on kidney burden, clinical applications in the old people should take into consideration the reduction and regular monitoring of kidney function [31]. In addition, from the animal experiments on quinolone antibiotics, it was found that young animals taking quinolone antibiotics would produce cartilage damage to joint tissue, so children, pregnant and lactating women should be forbidden levofloxacin [32][33][34][35]. At the same time, because levofloxacin belongs to quinolones antibiotic effect, from this group of cases cure effect and ADRs of reaction after taking levofloxacin, static drop 1-or 2-times daily fee sand star of left oxygen drugs for prevention of postoperative infection, there was no significant difference, and oxygen cost effect of medication to reduce the incidence of ADR is safer and more effective [36][37][38][39].…”
mentioning
confidence: 99%
“…Over 60 years old in patients receiving levofloxacin there was a higher incidence of adverse reactions to prevent infection treatment mainly includes: the main reasons for elderly patients with viscera function decline, easily complicated by a variety of disease, and levofloxacin by kidney metabolism, effects on kidney burden, clinical applications in the old people should take into consideration the reduction and regular monitoring of kidney function [31]. In addition, from the animal experiments on quinolone antibiotics, it was found that young animals taking quinolone antibiotics would produce cartilage damage to joint tissue, so children, pregnant and lactating women should be forbidden levofloxacin [32][33][34][35]. At the same time, because levofloxacin belongs to quinolones antibiotic effect, from this group of cases cure effect and ADRs of reaction after taking levofloxacin, static drop 1-or 2-times daily fee sand star of left oxygen drugs for prevention of postoperative infection, there was no significant difference, and oxygen cost effect of medication to reduce the incidence of ADR is safer and more effective [36][37][38][39].…”
mentioning
confidence: 99%
“…Lastly, more rigorous PopPK analyses to determine the optimal starting dose, if performed at local or regional levels, may be able to determine a setting-specific dose that could mitigate the routine need for TDM. [55][56][57]…”
mentioning
confidence: 99%
“…For RR/MDR-TB, drugs of priority should include fluoroquinolones and pyrazinamide where in vitro and clinically identified targets now appear to align. Alternative sample matrices such as saliva [ 21 ] and urine [ 22 ] that use spectrophotometric methods may bring such personalized dosing closer to the point of care.…”
Section: Discussionmentioning
confidence: 99%